2023
DOI: 10.15252/embr.202357108
|View full text |Cite
|
Sign up to set email alerts
|

SETD1A function in leukemia is mediated through interaction with mitotic regulators BuGZ/BUB3

Abstract: The H3K4 methyltransferase SETD1A plays a crucial role in leukemia cell survival through its noncatalytic FLOS domain‐mediated recruitment of cyclin K and regulation of DNA damage response genes. In this study, we identify a functional nuclear localization signal in and interaction partners of the FLOS domain. Our screen for FLOS domain‐binding partners reveals that the SETD1A FLOS domain binds mitosis‐associated proteins BuGZ/BUB3. Inhibition of both cyclin K and BuGZ/BUB3‐binding motifs in SETD1A shows syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The overexpression of ZNF207 has been significantly associated with poor clinical outcomes in liver malignancies. Previous studies revealed the involvement of ZNF207 in the modulation of stem cell self-renewal and pluripotency, as well as its influence on chromosome arrangement. ,, Inhibiting ZNF207 affects the BUB3 mitotic checkpoint protein (BUB3) and BUB1 mitotic checkpoint serine/threonine kinase (BUB1) kinetochore localization, causing defects in spindle formation in GSCs and other transformed cells but not in human neural stem cells or nontransformed ones. Moreover, it has been observed that in p53-deficient CSCs, targeting ZNF207 might enhance the sensitivity of tumor cells to cisplatin by inhibiting spindle assembly checkpoints .…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of ZNF207 has been significantly associated with poor clinical outcomes in liver malignancies. Previous studies revealed the involvement of ZNF207 in the modulation of stem cell self-renewal and pluripotency, as well as its influence on chromosome arrangement. ,, Inhibiting ZNF207 affects the BUB3 mitotic checkpoint protein (BUB3) and BUB1 mitotic checkpoint serine/threonine kinase (BUB1) kinetochore localization, causing defects in spindle formation in GSCs and other transformed cells but not in human neural stem cells or nontransformed ones. Moreover, it has been observed that in p53-deficient CSCs, targeting ZNF207 might enhance the sensitivity of tumor cells to cisplatin by inhibiting spindle assembly checkpoints .…”
Section: Introductionmentioning
confidence: 99%